A Delphi Consensus report from the "Prolonged Air Leak: A Survey" study group on prevention and management of postoperative air leaks after minimally invasive anatomical resections. (4th April 2022) - Zaraca, Francesco; Brunelli, Alessandro; Pipitone, Marco Damiano; Abdellateef, Amr; Abu Akar, Firas; Augustin, Florian; Batchelor, Tim; Bertani, Alessandro; Crisci, Roberto; D'Amico, Thomas; D'Journo, Xavier Benoit; Droghetti, Andrea; et al.
Abstract: OBJECTIVES: This study reports the results of an international expert consensus process evaluating the assessment of intraoperative air leaks (IAL) and treatment of postoperative prolonged air leaks (PAL) utilizing a Delphi process, with the aim of helping standardization and improving practice. METHODS: A panel of 45 questions was developed and submitted to an international working group of experts in minimally invasive lung cancer surgery. Modified Delphi methodology was used to review responses, including 3 rounds of voting. The consensus was defined a priori as >50% agreement among the experts. Clinical practice standards were graded as recommended or highly recommended if 50–74% or >75% of the experts reached an agreement, respectively. RESULTS: A total of 32 experts from 18 countries completed the questionnaires in all 3 rounds. Respondents agreed that PAL are defined as >5 days and that current risk models are rarely used. The consensus was reached in 33/45 issues (73.3%). IAL were classified as mild (<100 ml/min; 81%), moderate (100–400 ml/min; 71%) and severe (>400 ml/min; 74%). If mild IAL are detected, 68% do not treat; if moderate, consensus was not; if severe, 90% favoured treatment. CONCLUSIONS: This expert consensus working group reached an agreement on the majority of issues regarding the detection and management of IAL and PAL. In the absence of prospective, randomized evidence supporting most of these clinical decisions, this document may serve as a guideline to reduce practice variation. Abstract : Prolonged air leak (PAL) after pulmonary resection is a common complication, with a significant impact on the duration of the hospital stay after surgery.